Designing Emotionally Adaptive Interfaces: Affective Ux Model For Enhancing Engagement In Gamified Learning Apps - Dinata, Adjeng Rahayu; Hardiansyah, Firli; Sari, Juita Fitriana (University of Science and Computer Technology, 2025)
In the digital learning era, user engagement is shaped not only by functionality and aesthetics but also by how interfaces adapt to users’ emotional experiences. While gamified learning environments have become common, few designs systematically integrate affective computing principles to support real-time emotional adaptation. This study proposes an Affective UX Model that combines affective computing with user experience (UX) design to enhance emotional engagement in gamified educational interfaces. The research aims to explore how emotionally adaptive features can be designed, implemented, and evaluated within a learning context. Using a user-centered design (UCD) approach, the study employed mixed methods, including visual storytelling, interactive prototyping, and affective mapping via self-report measures and biometric tracking (facial expressions and heart rate variability). A gamified language-learning prototype was tested with 30 adolescent participants (aged 15–18) through usability and emotional response evaluations. Results show that empathetic avatars, responsive feedback, and adaptive difficulty adjustments significantly increased motivation, engagement, and emotional comfort. Participants reported a stronger sense of connection when system feedback matched their affective State and performance. The study contributes a validated conceptual framework for designing emotionally intelligent, human-centered educational interfaces, emphasizing how affective adaptivity enhances the quality of user experience and learning outcomes. The findings demonstrate that dynamic emotional adaptation can redefine engagement and inform future directions in emotionally responsive design research.